Lung Cancer: Posttreatment Imaging. Issue 5 (September 2017) - Benveniste, Marcelo F.; Gomez, Daniel; Viswanathan, Chitra; Shroff, Girish S.; Betancourt Cuellar, Sonia L.; Carter, Brett W.; Marom, Edith M.
Abstract : Over the last few decades, advances in radiation therapy technology have markedly improved radiation delivery. Advancements in treatment planning with the development of image-guided radiotherapy and techniques such as proton therapy, allow precise delivery of high doses of radiation conformed to the tumor. These advancements result in improved locoregional control while reducing radiation dose to surrounding normal tissue. The radiologic manifestations of these techniques can differ from radiation induced lung disease seen with traditional radiation therapy. Awareness of these radiologic manifestations and correlation with radiation treatment plans are important to differentiate expected radiation induced lung injury from recurrence, infection and drug toxicity.